Contemporary Studies in the Evolution of Accounting Thought (Book). - Sterling, Robert R.; Pattillo, James W. (The Accounting Review, 1970)
Reviews the book "Contemporary Studies in the Evolution of Accounting Thought," by Michael Chatfield.